Case Study of the Sinking of the KLM Fajar Lorena Safari in Situbondo Waters, Reviewed Based on Statistical Data from the Perak-Surabaya Meteorology, Climatology, and Geophysics Agency (BMKG) - Napitupulu, Alexa (Universitas Hang Tuah, 2026)
Shipping safety in Indonesia still faces various challenges, one of which is the influence of the dynamics of the marine environment, particularly sea waves. This study examines the sinking of the Motor Sailing Ship (KLM) Fajar Lorena Safari that occurred in Situbondo Waters on December 8, 2024, at 1:00 PM WIB by reviewing sea wave conditions based on statistical data from the BMKG Perak Maritime Meteorology Station in Surabaya. The analysis was conducted by linking the parameters of significant wave height, wind direction and speed, and surface currents to the ship's dynamic response from the perspective of wave physics and fluid mechanics. The results of the study indicate that although the significant wave height at the time of the incident was relatively low, changes in wind direction and wave-current interactions have the potential to trigger cross waves that increase rolling motion and reduce the stability of traditional wooden ships. This condition is exacerbated by the limited dynamic stability of the ship and the possibility of water ingress into the hull. These findings emphasize that ship accidents are not always triggered by high waves, but rather by a combination of oceanographic factors and ship characteristics. Therefore, utilizing BMKG early warnings and understanding wave dynamics are important in efforts to mitigate shipping risks.